(untitled) (Journal of the Management Sciences, 2025)
This study examines the factors contributing to concealment of health information among men, and its relevance towards preventable mortality within the psychological, social, cultural, and economic contexts. The study was carried out in Anambra State South Senatorial District, Nigeria and anchored on the Health Belief Model (HBM) and Hegemonic Masculinity Theory (HMT). The study expands theory by incorporating economic and socio-cultural factors, providing strategies to mitigate mortality associated with hidden health conditions. With a cross-sectional survey approach, data were collected from 400 respondents sampled through multistage sampling using a validated 5-point Likert scale instrument. Data were analysed using mean and standard deviation calculations. Study findings show that men more often conceal illnesses from fear of being ridiculed, considered weak, and because of financial constraints. This supports HBM’s psychological dimensions and HMT’s focus on masculine ideals. It concluded that most men conceal their health status primarily due to show of masculinity. The study recommended interventions such as community-based programmes focusing on economic concerns and stigma abstinence, campaigns promoting positive masculinity that redefine strength, and collaboration with religious and cultural figures to change norms regarding disclosure.